Pidana Aborsi Dalam KUHP - Nurhayana Khofifah Adisty Sagala; Nazli Khatami; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This research was conducted using a normative juridical approach because it uses secondary data as the main data source, which is based on primary legal materials, namely the criminal law code, law no. 36 of 2009 concerning Health, secondary legal material in the form of references to several existing journals, notes and other sources. The results of the study can be concluded that only the Health law allows a woman to have an abortion on the grounds of hereditary disease which causes the baby to be physically disabled. And the implementation of handling the criminal act of abortion for any reason is prohibited according to the criminal law code. Therefore, it is hoped that law enforcers can provide severe and appropriate punishment to the perpetrators of the abortion, so that the perpetrators get a deterrent effect on the abortion they perform. Therefore, several places that are prone to having an abortion must be monitored and checked, so that abortion activities do not occur, which are prohibited by law. According to Law No. 36 of 2009 concerning Health, it is only permissible for a woman to have an abortion in a medical condition. Because even though the abortion process had an impact on the woman who was aborted. Meanwhile, according to the law, Article 346 of the Criminal Code states that the threat of imprisonment for 4 years is for a woman who deliberately or orders another person to kill or abort her womb. keywords: crime, abortion, KUHP